Older women’s perceptions of HPV self-sampling and HPV-sampling performed by a midwife – a phenomenographic study - Nyman, Maria Hälleberg; Lillsunde Larsson, Gabriella; Blomberg, Karin; Schröder, Agneta (BMC public health, 2024)
Background Cervical cancer is a global disease and it is well established that cervical cancer is caused by human papillomavirus (HPV). In Sweden self-sampling for HPV is now used as a complement to sampling performed by a midwife. However, there is a lack of knowledge on how older women perceive the self-sampling compared to the sampling performed by a midwife. Therefore, the aim of the study was to describe how women, aged 64 years and older, perceived the process of self-sampling and sampling performed by a midwife for HPV-testing. Methods Eighteen women were included in a qualitative interview study, and a phenomenographic approach was used for the analysis of the interviews. Results Three descriptive categories emerged: Confidence in sampling, Facilitating participation and Being informed. Within the categories, eight conceptions emerged describing the variation relating to how the women perceived the process of self-sampling and sampling performed by a midwife. Conclusions Women in this study describe confidence in self-sampling for HPV-testing and that the self-sampling was saving time and money, both for themselves and for society. Information in relation to an HPV-positive test result is of importance and it must be kept in mind that women affected by HPV may feel guilt and shame, which health care professionals should pay attention to. This knowledge can be used in education of health care staff. Trial registration https://researchweb.org/is/fourol/project/228071 . Reg. no 228,071.